Comparison of nuclear abnormalities in Astyanax bifasciatus Cuvier, 1819 (Teleostei: Characidae) of two sections of rivers from the middle Iguaçu - Merieli Melo-Silva (Acta Scientiarum. Biological Sciences, 2018)
Most changes in water bodies are result of human activities that have the potential to undermine the environmental integrity of aquatic ecosystems. Changes in genetic material can be evidenced by the frequency of nuclear abnormalities in fish blood cells, in response to genotoxic agents even at low concentrations. Thus, we aimed at comparing the frequencies of nuclear abnormalities of fish kept in acclimation, with fish collected in Timbó river (Santa Cruz do Timbó, Santa Catarina State), under low anthropogenic interference, and fish collected in Iguaçu river (União da Vitória, Paraná State), a polluted river. The highest frequency of changes in nuclear morphology of fish erythrocytes was found in the urbanized area around the Iguaçu river, while, the fish collected in areas with preserved riparian forest surrounding the Timbó river and acclimated fish showed no morphological changes. Our results suggest that genotoxic compounds in the Iguaçu river are acting as stressors to aquatic communities, especially fish. In addition, the absence of nuclear abnormalities in fish from the Timbó river suggests that rivers without significant environmental changes can serve as reference point for comparative studies of genetic modifications for the species studied.